TAFSIR MUQARAN AYAT POLIGAMI DALAM KITAB TAFSIR AL-MANAR DAN AL-MUNIR: Telaah Terhadap Surat Al-Nisa Ayat 3 - Abidin, Alhadi Zaenal; Abidin, Ahmad Zainal; Rofi’ah, Karinatur (Al-Mufassir: Jurnal Ilmu Alquran, Tafsir dan Studi Islam, 2024)
The discourse and practice of polygamy in Islam still gives rise to differences of opinion. The same thing happens among commentators. This study analyzes al-Nisa` chapter verse 3 which incidentally is often used as a reference in polygamy from the perspective of the thoughts of two contemporary interpretive figures with different scientific and socio-historical backgrounds, namely Muhammad Abduh in Tafsir Al-Manar and Wahbah Az-Zuhaili in Tafsir Al-Munir. This comparative descriptive research is a literature review. This research attempts to find similarities and differences between two figures regarding the meaning of  An-Nisa` chapter verse 3, especially regarding polygamy. The results of this research show that Muhammad Abduh views polygamy as something that is very difficult for someone to do in the current era. This cannot be separated from the requirements of polygamy, namely finding justice, especially inner justice, which is difficult to realize and the resulting impact is more likely to cause harm or damage. Meanwhile, Wahbah Az-Zuhaili tends to relax the practice of polygamy, for example in various conditions, such as barren wives, large numbers of women and the interpretation of the concept of material justice. The differences between the two figures occur due to socio-historical conditions and the methods used in interpreting a verse. Muhammad Abduh tends to use his rational mind in interpreting a verse. Meanwhile, Wahbah Az-Zuhaili refers to the textual reasoning of the Koran. However, both have similarities in that they both make the concept of justice an absolute requirement for someone to allow polygamy.